2021
DOI: 10.1038/s41598-021-90659-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobile sonouroflowmetry using voiding sound and volume

Abstract: Uroflowmetry (UF) is a common clinic-based non-invasive test to diagnose Lower Urinary Tract Dysfunction (LUTD). Accurate home-based uroflowmetry methods are needed to conveniently conduct repeated uroflowmetries when patients are physiologically ready to urinate. To this end, we propose and evaluate a novel mobile sonouroflowmetry (SUF) method that estimates the urinary flow rate from a sound signal recorded using a mobile phone. By linearly mapping the total sound energy to the total voided volume, the sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Uroflowmetry entails the measurement of parameters such as voided volume, maximum and minimum flow rate, which collectively provides insights into the normal and abnormal conditions of the urinary tract. [ 52 ] Alternatively, acoustic uroflowmetry, [ 53 ] and mobile sonouroflowmetry [ 54 ] have been demonstrated and validated for the same purpose. Figure summarizes the schematic of the simulated urination process using disposable TENG (Di‐TENG) as a sensor tool and its detailed signal processing steps coupled with an AI algorithm for evaluating the urination condition.…”
Section: Resultsmentioning
confidence: 99%
“…Uroflowmetry entails the measurement of parameters such as voided volume, maximum and minimum flow rate, which collectively provides insights into the normal and abnormal conditions of the urinary tract. [ 52 ] Alternatively, acoustic uroflowmetry, [ 53 ] and mobile sonouroflowmetry [ 54 ] have been demonstrated and validated for the same purpose. Figure summarizes the schematic of the simulated urination process using disposable TENG (Di‐TENG) as a sensor tool and its detailed signal processing steps coupled with an AI algorithm for evaluating the urination condition.…”
Section: Resultsmentioning
confidence: 99%
“…13 Among our studies, only Lee et al that included pathologic subjects and the rest tested only with control populations. 5,14,15 As only one study included female participants, 16 the accuracy and reliability of sonouroflowmetry in this group remain unknown when compared to conventional uroflowmetry. This might be attributed to the difference in the needs of toiletries (e.g., toilet shapes, size, and amount of water needed) between male and female, especially as female needs more facilities as compared to male.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Three studies reported highly significant correlation in the average flow rate between Sono and conventional uroflowmetry. [13][14][15] Figure 1C shows the pooled correlation of the a5erage flow rate between tests, ranging from 0.7 to 0.85. Based on the analysis, a high heterogeneity was found (I 2 = 96.62% [95% CI: 93.84%-98.14%]).…”
Section: • Average Flow Ratementioning
confidence: 99%
“…Echoing the technology used in the Swan‐Ganz catheter to estimate cardiac output, 18 Viarani et al 19 described a temperature sensor that measures uroflow as the urine cools down by its passage through the apparatus' two membranes. Kato et al 20 used a turbine sensor allied with Bluetooth technology, and Helou et al 21 were able to produce a voiding curve with the sound of the voiding stream.…”
Section: Discussionmentioning
confidence: 99%